A Critical Analysis of the Transgender Persons (Protection of Rights) Act: Toward Inclusive and Affirmative Legal Reform - Tabassum, Nihal (Advances in Psychological Sciences and Applications, 2025)
This article critically examines the Transgender Persons (Protection of Rights) Act, 2018 and its 2022 amendment bill, with a focus on the definitional gaps that hinder its effective implementation. Central to the critique is the Act's failure to provide a clear and inclusive definition of the term "transgender," resulting in legal ambiguity and inconsistent application. Despite its progressive intent, the legislation has faced backlash from segments of society, often conflating gender identity rights with debates around same-sex relationships and LGBTQ+ (individuals who are lesbian, gay, bisexual, transgender, queer) recognition. The study adopts analytical and descriptive legal methods to explore the constitutional implications of the Act, its reception within Pakistani society, and its impact on the transgender community's access to fundamental rights, including education, healthcare, employment, and political participation. The article further assesses challenges related to gender identity recognition, kinship, inheritance, and marriage, and argues for a more precise and inclusive legal framework. Ultimately, this study advocates for pragmatic reforms that ensure the legislation serves as a robust instrument for the protection and empowerment of transgender individuals in Pakistan.